(untitled) (Nexus International Journal of Science and Education, 2024)
This study unearthed the experiences of k-3 teachers in implementing mother-tongue-based multilingual education in the Davao del Sur Division. Ten (10) K-3 teachers implemented the mother tongue-based multilingual education in teaching the subjects who participated in the study. This study used a phenomenological approach to extract the participants' ideas. The virtual in-depth interview was employed to gather some information regarding their respective narratives as they implemented the mother tongue-based multilingual education to enhance the learning outcome of K-3 learners. The thematic analysis of the responses from the participants of the study revealed the positive and negative experiences of k-3 teachers as they implemented mother tongue-based multilingual education and delved into (positive) strengthened cultural identity and confidence, gaining positive support from stakeholders and improved curriculum skills. On a negative note, insufficient instructional materials, compliance with compulsion, and insubstantial teacher training. The limited learning resources affected the implementation and caused struggles in the delivery of the curriculum. However, the K-3 teachers employed the following coping mechanisms: peer collaboration and co-teaching, attending language proficiency training, and capacitating teachers to use Mother Tongue. These mechanisms enabled the K-3 teachers to have a smooth implementation despite the limitations of teachers’ experiences. The insights drawn from the study's findings were social development, contribution to MAEM, and development of teachers’ expertise.